Crafting Uneven Waterscapes: The Well, the Tank, and the Racialised Contestation of Early Water Infrastructure in Colonial Durban, 1854-1898 - Brig-Ortiz, Kristin (South African Historical Journal, 2024)
Following borough incorporation in 1854, Durban took control of and built on the existing spiderwebbed networks of wells and tanks to maintain a clean water supply until the introduction of piped water. As Durban grew in size and racial make-up during the second half of the nineteenth century, the borough paid increasing attention to the state of the stand-alone water supply system and the public health threats it generated. It implemented racialised restrictions and policies around wells and tanks that depended on blurring the lines between publicly and privately owned water infrastructure. Although scholars have investigated the construction and use of piped waterworks in colonial sites, few have explored the importance of autonomous infrastructure and its persistence in the urban environment even after piped infrastructure is implemented, particularly in a significant British imperial port town like Durban. The examination of urban relationships to autonomous infrastructures like wells and tanks exposes how a racial capitalistic logic and social norming influenced who received access to water supplies and the kinds of technologies available to them.